2010
DOI: 10.1590/s0004-27302010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is not associated with vascular dysfunction in a model of alloxan-induced diabetic rats

Abstract: Objectives:To verify if an experimental model of alloxan-diabetic rats promotes oxidative stress, reduces nitric oxide bioavailability and causes vascular dysfunction, and to evaluate the effect of N-acetylcysteine (NAC) on these parameters. Methods: Alloxan-diabetic rats were treated or not with NAC for four weeks. Plasmatic levels of malondialdehyde (MDA) and nitrite/ nitrate (NOx), the endothelial and inducible nitric oxide synthase (eNOS and iNOS) immunostaining and the vascular reactivity of aorta were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The “common soil” theory of Ceriello et al [15,16] holds that oxidative stress is a common feature of insulin resistance, diabetes mellitus and cerebrovascular diseases [17]. In a body suffering from various harmful stimuli, there is an increase in free radicals and decreased elimination of those radicals can upset the balance of the oxidation system and antioxidant system, and damage tissues and function [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…The “common soil” theory of Ceriello et al [15,16] holds that oxidative stress is a common feature of insulin resistance, diabetes mellitus and cerebrovascular diseases [17]. In a body suffering from various harmful stimuli, there is an increase in free radicals and decreased elimination of those radicals can upset the balance of the oxidation system and antioxidant system, and damage tissues and function [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…[27] Treatment with SMC showed improvement in the myelination and degenerative changes of the nerve fiber in both the groups. Even though a complete restoration of neuronal integrity is not evident, a delay in the progression of diabetic neuropathy is obvious under the action of the SMC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that NAC treatment is able to decrease the MDA levels in diabetes. [11,20,32] However, Capellini et al, [29] did not find a positive result with regard to the MDA levels after NAC supplement [Values are means ± S.E from five animals/group; *P < 0.05 as compared to control/saline group, **P < 0.05 as compared to diabetic/ saline group in diabetes. In our study, the plasma levels of MDA were not altered in diabetic rats treated with NAC, as shown in the Table 4.…”
Section: Discussionmentioning
confidence: 98%
“…[29] Possibly the destruction of pancreatic beta cells by alloxan-induced ROS generation [19] hindered the potentially therapeutic effect of NAC on these cells, and consequently on the hyperglycemia status. In this aspect, perhaps the injection of NAC simultaneously with alloxan, in rats, prevents necrosis of pancreatic beta cells caused by ROS generation, [30] allowing for the proper functioning of the pancreas, and hence, insulin release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation